2018
DOI: 10.5296/jse.v8i3.13396
|View full text |Cite
|
Sign up to set email alerts
|

Training Adequacy and Pedagogic Practices of Teachers in Reception Facilities for Refugee Education in Greece during the Economic Crisis: A Case Study

Abstract: This research paper, which uses Basil Bernstein's theoretical framework, aims to search the training adequacy of the teachers who work in Reception Facilities for Refugee Education (RFRE) and to examine the pedagogic practices that they use at the micro-level of the school classroom. Teachers who worked in a RFRE in Greece participated in this research, which was conducted with the use of the semi-structured interview research tool. The findings showed the following: a) the insufficient training that the RFRE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Presently, studies on U-shape classroom learning spaces have indicated increased chances for interaction among students, increased classroom discussions, more student-teacher out-of-class consultations, and improved grades and test scores, when compared to classes that are a par held in traditional seating patterns [ [39] , [40] , [41] , [42] , [43] , [44] ].…”
Section: Discussionmentioning
confidence: 99%
“…Presently, studies on U-shape classroom learning spaces have indicated increased chances for interaction among students, increased classroom discussions, more student-teacher out-of-class consultations, and improved grades and test scores, when compared to classes that are a par held in traditional seating patterns [ [39] , [40] , [41] , [42] , [43] , [44] ].…”
Section: Discussionmentioning
confidence: 99%
“…As far as the organizational part of the training is concerned, it is obvious that there is lack of organized facilities, suitable educational material and sufficient tools (Asimaki et al, 2018;Mogli et al, 2020). That is why it is a challenge for teachers to create an environment as hospitable as possible considering what they are providedwith.…”
Section: Challenges In Teaching Refugee Studentsmentioning
confidence: 99%
“…Closely interwoven with the concept of code in Bernstein's theoretical framework, are the concepts of classification and framing (Asimaki, Lagiou, Koustourakis & Sakkoulis, 2018;Bernstein, 1989Bernstein, , 1990Koustourakis, 2018a). More specifically, classification depends on the power which determines what can be placed with what to form a category.…”
Section: Theoretical Notesmentioning
confidence: 99%
“…Bernstein (1989Bernstein ( , 2000, assigns particular importance to the pedagogical relationship that develops between teachers and pupils, maintaining that its internal logic is based on three interconnected rules: (a) the hierarchical rules, which are necessary for shaping the appropriate behavior in each pedagogical relationship and which are linked to learning the roles of transmitter and receiver, which define rules of conduct, morals and social order, and (b) the rules of sequencing and pacing which concern the order in which school knowledge is transmitted, as well as the time frame for the pupils to acquire it (Bernstein, 1989: 115). Finally, through the acquisition and implementation of the criteria rules, the pupil understands which forms of communication, social relationship or position in the school field are permitted, and which not (Asimaki et al, 2018;Bernstein, 2000;Koustourakis, 2018a). Bernstein (1989Bernstein ( , 1990 proposes a model for the investigation of pedagogical practices that can reveal and interpret the interactions between teachers and pupils on the micro-level of the school classrooms that take place for the realization of the daily educational work.…”
Section: Theoretical Notesmentioning
confidence: 99%